2017
DOI: 10.1111/aogs.13210
|View full text |Cite
|
Sign up to set email alerts
|

Is the incidence of recurrent pregnancy loss increasing? A retrospective register‐based study in Sweden

Abstract: This study suggests that the incidence of RPL increased during the 10-year period studied. Causes can only be speculated upon in this study design, but might be associated with environmental changes, as the increase was fairly rapid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 30 publications
2
53
0
1
Order By: Relevance
“…evaluated Swedish women who were pregnant between 2003 and 2012 and found a 58% increase in the number of new cases of RPL (three or more prior miscarriages) during this period. The authors suggested that this significant increase in the incidence is because of couples' decisions to conceive later in life and obesity …”
Section: Introductionmentioning
confidence: 99%
“…evaluated Swedish women who were pregnant between 2003 and 2012 and found a 58% increase in the number of new cases of RPL (three or more prior miscarriages) during this period. The authors suggested that this significant increase in the incidence is because of couples' decisions to conceive later in life and obesity …”
Section: Introductionmentioning
confidence: 99%
“…11 Two Scandinavian studies found that 40-48% of cases were secondary RPL. 1,12 One study from Israel reported that 61% of cases were secondary RPL. 13 RPL is a multifactorial condition that in addition to fetal causes have multiple known female risk factors such as autoimmune diseases, endocrine disorders, and uterine malformations.…”
Section: Introductionmentioning
confidence: 99%
“…The most appropriate definition of RPL is three or more consecutive miscarriages before gestational week 22 (gestational age 21 weeks +6 days) . According to this, the incidence of RPL is estimated to vary between 0.5 and 2.3% in different populations . However, some define RPL as two or more miscarriages .…”
Section: Introductionmentioning
confidence: 99%